Mechanisms of Effective Governance and Cooperation: Comparative Analysis of the European States - Hurnyak, Ihor; Kordonska, Aleksandra (Przegląd Wschodnioeuropejski, 2021)
The research performs an attempt to adapt accumulated approaches of the Institutional Economics to the application of the Coase theorem in public administration. Governance is mainly analyzed in the field of political science, while transactional costs definitely serve to the economic surveys. Solving the problem of social costs, Coase theorem revealed a conception of property rights as the outcome of mere contracting in independent exchanges. This conception is applicable for analyzing a wide range of issues, including externalities related to the use of assets and public goods. The article contains a brief characteristic of the self-governance in European states. The results of comparative analysis of the local governance in European region became a basis for proposing a series of transformation tools for Ukraine and neighboring states in this field. Obtained results of statistical modeling and payoff matrix of Nash equilibrium clearly confirm the validity of the Coase theorem for interpretation of the interaction between local self-governance and government institutions.